Pore surface engineering in porous, chemically stable covalent organic frameworks for water adsorption - Biswal, Bishnu P.; Kandambeth, Sharath; Chandra, Suman; Shinde, Digambar Balaji; Bera, Saibal; Karak, Suvendu; Garai, Bikash; Kharul, Ulhas K.; Banerjee, Rahul (Journal of Materials Chemistry A, 2015)
Herein, we have explored the possibility of a class of covalent organic frameworks (COFs) as water adsorbing materials. We have selected, synthesized 12 chemically stable functionalized Schiff base COFs and thoroughly studied their water uptake behaviour. Further, a deep understanding was developed with these COFs towards the effects of condensation pressure of water and hydrophilic/hydrophobic groups present in the COF pores on water absorption capacity and ultimately, their recyclability. Among all reported COFs, TpPa-1 shows the highest water uptake of 30 wt% (368 cm(3) g(-1); 17 mmol g(-1)) at P/P-0 = 0.3, which is also comparable with the recently reported carbon materials and few well known MOFs. This study also reveals that the overall water uptake of COFs can be tuned systematically based on chemical functionality and pore size in a wider window of relative pressures.

Facile strategy for accessing 3-alkynylchromones through gold-catalyzed alkynylation/cyclization of o-hydroxyarylenaminones - Akram, Manjur O.; Bera, Saibal; Patil, Nitin T. (Chemical Communications, 2016)
A strategy based on tandem alkynylation of o-hydroxyarylenaminones followed by intramolecular cyclization has been developed to generate a diverse array of 3-alkynyl chromones. The functionality embedded in these key intermediates enables their facile elaboration into more diverse structures by a variety of functionalizations and ring-forming processes.

[3+2]-Annulation of platinum-bound azomethine ylides with distal C[double bond, length as m-dash]C bonds of N-allenamides - Chakrabarty, Indradweep; Inamdar, Suleman M.; Akram, Manjur O.; Gade, Amol B.; Banerjee, Subhrashis; Bera, Saibal; Patil, Nitin T. (Chemical Communications, 2017)
A Pt-catalyzed, highly regioselective reaction between N-allenamides and imino-alkynes leading to pyrrolo[1,2-a] indoles is described. This represents the first example of [3+2]-annulation of Pt-bound azomethine ylides with the distal CQC bond of N-allenamides. The mechanism of the reaction was established by computational studies.

Interplaying anions in a supramolecular metallohydrogel to form metal organic frameworks - Karak, Suvendu; Kumar, Sushil; Bera, Saibal; Diaz Diaz, David; Banerjee, Subhrashis; Vanka, Kumar; Banerjee, Rahul (Chemical Communications, 2017)
The remarkable effect of anions on the transition from supramolecular gels to crystalline phases has been described. An amino acid-based metallohydrogel was transformed into different metal-organic frameworks through the selective picking of anions. The metallohydrogel and the resulting metal-organic frameworks (MOFs) were thoroughly characterized. The results demonstrated controlled access over the binding of a particular anion to selectively form a particular MOF.

Interlayer hydrogen-bonded covalent organic frameworks as high-performance supercapacitors - Halder, Arjun; Ghosh, Meena; Khayum, Abdul M.; Bera, Saibal; Addicoat, Matthew; Sasmal, Himadri Sekhar; Karak, Suvendu; Kurungot, Sreekumar; Banerjee, Rahul (Journal of the American Chemical Society, 2018)
Covalent organic frameworks (COFs) have emerged as promising electrode materials in supercapacitors (SCs). However, their insoluble powder-like nature, poor capacitive performance in pristine form, integrated with inferior electrochemical stability is a primary concern for their long-term use in electrochemical devices. Keeping this in perspective, herein we report a redox active and hydrogen bonded COF with ultrahigh stability in conc. H2SO4 (18 M), conc. HCl (12 M) and NaOH (9 M). The as-synthesized COF fabricated as thin sheets were efficiently employed as a free-standing supercapacitor electrode material using 3 M aq. H2SO4 as an electrolyte. Moreover, the pristine COF sheet showcased outstanding areal capacitance 1600 mF cm(-2) (gravimetric 169 F g(-1)) and excellent cyclic stability (>100 000) without compromising its capacitive performance or Coulombic efficiency. Moreover, as a proof-of-concept, a solid-state supercapacitor device was also assembled and subsequently tested.

Multistimuli-responsive interconvertible low-molecular weight metallohydrogels and the in situ entrapment of CdS quantum dots therein - Bera, Saibal; Chakraborty, Amit; Karak, Suvendu; Halder, Arjun; Chatterjee, Soumyajyoti; Saha, Subhadeep; Banerjee, Rahul (Chemistry of Materials, 2018)
Two low molecular weight metallohydrogels (ZALA and CALA) have been synthesized from an amino-acid based ligand precursor (LA) and two different metal salts [zinc acetate dihydrate (ZA) and cadmium acetate dihydrate (CA), respectively. These two hydrogels show a unique chemically stimulated interconversion to each other via a reversible gel-sol gel pathway. This programmable gel-sol reversible system satisfies logic operations of a basic Boolean logic (INHIBIT) gate. Also, these hydrogels can be degraded into different MOF phases at room temperature spontaneously or in the presence of chloride and bromide salts (NaCl and NaBr.). CdS quantum dots can be grown inside the CALA gel matrix (CdS@CALA) in the presence of small amount of Na2S. This CdS doped gel exhibits time dependent tunable emission (white to yellow to orange) as a consequence of a slow agglomeration process of the entrapped quantum dots inside the gel matrix. This luminescence property also reflects the corresponding gel derived MOFs (obtained either by self-degradation of CdS@CALA or via anion induction) as well. This, to the best of our knowledge, is probably the simplest way to make a CdS quantum dot based composite material where CdS is entrapped within the gel and the gel-derived MOF matrix.

Ultrastable imine-based covalent organic frameworks for sulfuric acid recovery: an effect of interlayer hydrogen bonding - Halder, Arjun; Karak, Suvendu; Addicoat, Matthew; Bera, Saibal; Chakraborty, Amit; Kunjattu, Shebeeb H.; Pachfule, Pradip; Heine, Thomas; Banerjee, Rahul (Angewandte Chemie-International Edition, 2018)
A rapid and scalable synthesis of six new imine-linked highly porous and crystalline COFs is presented that feature exceptionally high chemical stability in harsh environments including conc. H2SO4 (18M), conc. HCl (12M), and NaOH (9M). This is because of the presence of strong interlayer C-H center dot center dot center dot N hydrogen bonding among the individual layers, which provides significant steric hindrance and a hydrophobic environment around the imine (-C=N-) bonds, thus preventing their hydrolysis in such an abrasive environment. These COFs were further converted into porous, crystalline, self-standing, and crack-free COF membranes (COFMs) with extremely high chemical stability for their potential applications for sulfuric acid recovery. The as-synthesized COFMs exhibit unprecedented permeance for acetonitrile (280 Lm(-2) h(-1) bar(-1)) and acetone (260 Lm(-2) h(-1) bar(-1)).

External oxidant-dependent reactivity switch in copper-mediated intramolecular carboamination of alkynes: access to a different class of fluorescent ionic nitrogen-doped polycyclic aromatic hydrocarbons - Shaikh, Aslam C.; Banerjee, Somsuvra; Mule, Ravindra D.; Bera, Saibal; Patil, Nitin T. (Journal of Organic Chemistry, 2019)
An interesting case of external oxidant-controlled reactivity switch leading to a divergent set of ionic nitrogen-doped polycyclic aromatic hydrocarbons (N-doped PAHs), is presented here, which is quite unrecognized in copper-mediated reactions. In the current scenario, from the same pyridino-alkyne substrates, the use of the external oxidant Ph1(0Ac)2, in combination with Cu(OTf)(2), gave N-doped spiro-PAHs via a dearomative 1,2-carboamination process; whereas, without the use of oxidant, an alkyne/azadiene [4 + 2]-cycloaddition cascade occurred to exclusively afford ionic N-doped PAHs. These newly synthesized N-doped PAHs further exhibit tunable emissions, as well as excellent quantum efficiencies.

Inducing disorder in order: hierarchically porous covalent organic framework nanostructures for rapid removal of persistent organic pollutants - Karak, Suvendu; Dey, Kaushik; Torris, Arun; Halder, Arjun; Bera, Saibal; Kanheerampockil, Fayis; Banerjee, Rahul (Journal of the American Chemical Society, 2019)
The key factor responsible for fast diffusion and mass transfer through a porous material is the availability of a widely open pore interior having complete accessibility from their surface. However, because of their highly stacked nature, ordered two-dimensional (2D) materials fail to find real-world applicability, as it is difficult to take advantage of their complete structure, especially the inner cores. In this regard, three-dimensional (3D) nanostructures constructed from layered two-dimensional crystallites could prove to be advantageous. However, the real challenge is to cultivate a porous nanostructure with ordered pores where the pores are surrounded by crystalline walls. Herein, a simple yet versatile in situ gas-phase foaming technique has been employed to address these cardinal issues. The use of baking soda leads to the continuous effervescence of CO2 during the crystallization of foam, which creates ripples and fluctuations on the surface of the 2D crystallites. The induction of ordered micropores within the disordered 3D architecture synergistically renders fast diffusion of various guests through the interconnected pore network. The high-density defects in the hierarchically porous structure help in ultrafast adsorption (<10 s) of various pollutants (removal efficiency of 99%) from water, all of which would lead to significant environmental benefit. The pseudo-second-order rate constant for the BPA pollutant is 182.3 g mg(-1) min(-1), which is the highest among all the literature reports to date. The high removal efficiency (highest efficiency of 94% and average efficiency of 70%) of a persistent organic pollutant has been attended for the first time.

Porosity switching in polymorphic porous organic cages with exceptional chemical stability - Bera, Saibal; Dey, Kaushik; Pal, Tapan K.; Halder, Arjun; Tothadi, Srinu; Karak, Suvendu; Addicoat, Matthew; Banerjee, Rahul (Angewandte Chemie-International Edition, 2019)
Porous solids that can be switched between different forms with distinct physical properties are appealing candidates for separation, catalysis, and host-guest chemistry. In this regard, porous organic cages (POCs) are of profound interest because of their solution-state accessibility. However, the application of POCs is limited by poor chemical stability. Synthesis of an exceptionally stable imine-linked (4+6) porous organic cage (TpOMe-CDA) is reported using 2,4,6-trimethoxy-1,3,5-triformyl benzene (TpOMe) as a precursor aldehyde. Introduction of the -OMe functional group to the aldehyde creates significant steric and hydrophobic characteristics in the environment around the imine bonds that protects the cage molecules from hydrolysis in the presence of acids or bases. The electronic effect of the -OMe group also plays an important role in enhancing the stability of the reported POCs. As a consequence, TpOMe-CDA reveals exceptional chemical stability in neutral, acidic and basic conditions, even in 12m NaOH. Interestingly, TpOMe-CDA exists in three different porous and non-porous polymorphic forms (, , and ) with respect to differences in crystallographic packing and the orientation of the flexible methoxy groups. All of the polymorphs retain their crystallinity even after treatment with acids and bases. All the polymorphs of TpOMe-CDA differ significantly in their properties as well as morphology and could be reversibly switched in the presence of an external stimulus.
Keywords: chemical stability; Morphology; organic cages; polymorphism; porosity switching